Multiple Osteomas in Middle Ear. (24th July 2012) - Li, Yongxin; Li, Qiuhuan; Gong, Shusheng; Liu, Honggang; Yu, Zilong; Zhang, Luo
Abstract : Since the first description of middle ear osteomas by Thomas in 1964, only few reports were published within the English literatures (Greinwalid et al., 1998; Shimizu et al., 2003; Cho et al., 2005; and Jang et al., 2009), and only one case of the multiple osteomas in middle ear was described by Kim et al., 2006, which arose from the promontory, lateral semicircular canal, and epitympanum. Here we describe a patient with multiple middle ear osteomas arising from the promontory, incus, Eustachian tube, and bony semicanal of tensor tympani muscle. This patient also contracted the chronic otitis media in the ipsilateral ear. The osteomas were successfully removed by performing type III tympanoplasty in one stage.